Antimicrobial susceptibility and serovars of Salmonella from chickens and humans in Ibadan, Nigeria - Fashae, Kayode; Ogunsola, Folasade; Aarestrup, Frank M; Hendriksen, Rene S (The Journal of Infection in Developing Countries, 2010)
Background: This study determines the prevalence and antibiotic resistance of Salmonella serovars from humans and chickens in Ibadan, Nigeria, in 2004-2007. Methodology: A total of 991 blood samples were collected from patients in 2004 to 2005 and 641 fecal samples were collected from poultry farms in 2007. All Salmonella isolates were serotyped and tested for antimicrobial susceptibility. Results: Thirty-nine (4%) Salmonella isolates were obtained from human blood and 70 (11%) from chicken fecal samples. The human isolates revealed nine different serovars; 82% were non-typhoidal Salmonella and 18% were (S. Typhi). The majority of serovars from humans were S. Enteritidis (33%), S. Dublin (18%), and S. Typhimurium (18%). Resistance to chloramphenicol, sulfamethoxazole, trimethoprim, and ampicillin ranged from 36% to 59% for the human isolates. Eight different serovars were obtained from chickens; S. Virchow (71%) predominated. A high frequency (87%) of reduced susceptibility to ciprofloxacin was observed among the chicken isolates. A high frequency of resistance to tetracycline (93%), nalidixic acid (81%), and sulfamethoxazole (87%) was observed. Rare serovars such as S. Apapa, S. Mouschaui, S. Jukestown, S. Oritamerin, and S. Onireke were isolated from both humans and chickens. Identical serovars were not found among human and chicken isolates. Conclusions: This study indicates that chickens are not a reservoir of Salmonella causing bacteraemia among humans in Ibadan, Nigeria. Studies locating the reservoirs responsible for invasive salmonellosis in humans are needed. Controls and targeted interventions against S. Virchow and the frequent occurrence of antimicrobial resistance in chickens should be initiated to prevent the spread of this serovar.